Loboschiza Diakonoff (Lepidoptera: Tortricidae) from Thailand with descriptions of four new species - Anan, Surachet; Dokchan, Paradorn; Pinkaew, Nantasak (Zootaxa, 2016)
Four new species of Loboschiza Diakonoff collected from the Nakhon Ratchasima, Chanthaburi, Nakhon Nayok, Sa Kaeo, Nakhon Si Thammarat, and Nakhon Pathom provinces of Thailand are described: Loboschiza spiniforma Anan and Pinkaew, n. sp.; Loboschiza bisulca Anan and Pinkaew, n. sp.; Loboschiza subrectangula Anan and Pinkaew, n. sp.; and Loboschiza lunata Anan and Pinkaew, n. sp. Loboschiza koenigiana (Fabricius) is redescribed. Illustrations of adults and genitalia are provided.